Understanding the Sustainability Perspectives of City Tourism: Directions for Strategies and Future Research - Ravichandran, Sabari Shankar (Prabandhan: Indian Journal of Management, 2024)
Purpose : Due to the diversity of tourist objectives and corporate needs, city tourism creates sustainability issues. Resilience, digital communication, industrial integration, and novel sustainable branding strategies are required in the aftermath of the crisis. This research found limitations in the promotion of a sustainable future in city tourism. Methodology : While much research in the literature focuses on city tourism and tourist experiences, just a few studies consider a sustainable future. As a result, this communication was created as a research note based on the author’s review of current research data and contemplation on city tourism’s complicated state of the art. Findings : This research paper focused on venues based on the UNWTO 2019 City Tourism Performance Report, theoretical basis – destination image perspectives, omitted destination culture, destination cooperation, communication, and so on. Opportunities for sustainable branding and experimental research were also emphasized. Implications : This research note highlighted the potential research opportunities in city tourism studies, emphasizing the need for longitudinal, technological, community-centric, and comparative research to enhance sustainable city tourism and achieve the United Nations Sustainable Development Goals (UNSDGs) 2030. Originality/Value : Critical gaps in sustainable urban tourism were identified. The post-crisis circumstances of city tourism, including chances for resilience, digital methodologies, and community-centric initiatives, were mainly explored.